Does Corporate Governance Influence Enterprise Risk in India? An Analytical Study - Jacob, Sajit (Ushus Journal of Business Management, 2015)
This paper investigates the association between Corporate Governance (CG) performance and enterprise risk in India. The study also investigates the behavior of risk under different classifications. As part of this study, Risk is estimated through a Multifactor Estimation of VaR. with Cash Value Added being used as the covariate that represents the value of the firm. This study helps to rate the progress of enterprise risk governance reforms from the point of CG performance, plan further reforms and enable investors to choose the right firms. Policy makers will know where to focus, stakeholders will recognize their roles and responsibilities with respect to risk management and management will take informed operational decisions around the policies set. Major findings of the paper are: there exists significant risk on the extreme ends of the CGPI ordinal scale, CGPI influences CVA which in turn determines enterprise risk,CVA and risk analysis finds a significant role for industrial segments. Also the number of risk free companies in these extreme segments is the least. Manufacturing and service sectors carry maximum risk